Gaps in Teaching Comprehensive Sexuality Education: A Review of Literature - Pokharel, Sharmila; Devkota, Bhimsen (NPRC Journal of Multidisciplinary Research, 2026)
Background: Comprehensive Sexuality Education (CSE) is globally recognized as essential for adolescent development and sexual and reproductive health. However, a significant disconnect exists between international policy frameworks and actual classroom implementation, particularly in low- and middle-income countries.Objective: This review examines how CSE is taught to children aged 5–15 years, identifying implementation gaps across diverse socio-cultural contexts with special emphasis on Nepal, where progressive policies coexist with limited classroom practice.Methods: A systematic literature review of 45 peer-reviewed studies and grey literature published between 2010–2024 was conducted. Databases including Google Scholar, PubMed, and HINARI were searched using Boolean operators. Studies from over 15 countries (Nepal, South Africa, Nigeria, Uganda, the Netherlands, Japan, and the United States) were thematically analyzed using inductive and deductive approaches.Findings: Three major implementation gaps emerged: (1) inadequate teacher preparation and discomfort teaching sensitive topics; (2) socio-cultural and religious barriers creating classroom silence; and (3) reliance on outdated, lecture-based pedagogy rather than participatory methods. Students across contexts desire comprehensive sexual health information but rely on informal, often inaccurate sources. In Nepal, despite supportive policies, CSE remains fragmented, culturally shame-bound, and biologically focused, excluding critical topics like consent, gender equality, and sexual diversity.Conclusion: Effective CSE requires contextually adapted, rights-based curricula; specialized teacher training incorporating values reflection; and student-centered pedagogies. Anderson and Krathwohl’s revised taxonomy offers a framework for moving beyond factual recall toward critical thinking and practical skill development.Novelty: This review uniquely synthesizes global evidence on CSE teaching processes—not just content—while highlighting Nepal’s under-researched implementation challenges and proposing theoretically grounded, culturally responsive solutions.